Incorporating Photovoice in the Marketing Curriculum to Increase Cultural Competence. (April 2020) - Pierce, Meghan E.; Longo, Jaime L.
Images are powerful. They help make the abstract concrete and allow the viewer to share the perspective of the photographer, giving the photographer a platform to communicate what may be difficult to express with words. Educators, institutions, accreditors, and students are seeking diverse and inclusive university environments, yet we often lack the critical dialogue necessary for achieving such outcomes. In response to student and employer imperatives, we propose the inclusion of photovoice to complement existing learning outcomes in the marketing curriculum. We discuss the implementation and evaluation of including photovoice into a semester-long client-based marketing research project. Experiential learning with photovoice increased interactions with diverse others and increased metacognitive cultural intelligence in comparison with a section taught with the standard approach.